THE PRESENCE OF PLUMBUM (Pb) AND CADMIUM (Cd) HEAVY METALS OF BROILER CHICKEN - Zahra Layli Rochimi; Rahayu Sri Pujiati; Prehatin Tri Rahayu Ningrum (Universitas Medan Area, 2023)
The level of meat production from purebred chickens in East Java Province from 2009 to 2019 reached 510,535.29 tons. The existence of heavy metal contamination in chickens are dangerous for human health due to the lack of good facilities and infrastructure on broiler farms including land and locations that must be environmentally friendly, and when rearing chickens in paying attention to the needs of water and feed for broiler chickens that are not polluted by heavy metals. The objective of this study was to describe the levels of heavy metals in chicken meat at X Chicken Farm in Kertosari Village, Pakusari District, Jember Regency. This research was a type of descriptive research. The subjects of this study were 20 samples of broiler chicken, well water, and 4 respondents. The sampling technique used purposive sampling. Data analysis used descriptive to describe the use of chicken feed, sources of drinking water, and the presence of heavy metal levels of Pb and Cd in chicken. The result indicate that as many as 20 samples of chicken meat contained levels of heavy metals Pb and Cd below the quality standard values according to Indonesian Nasional Standard (SNI) 7387:2009), namely (pb 0.3/kg) and (Cd <0.0200) while for water drinking water used comes from drilled wells containing Pb 0.001 mg/l and Cd 0.001 mg/l..